Morphophysiological alterations caused by insertional mutagenesis of contactin 5 (Cntn5) gene in transgenic mice - A. V. Smirnov; N. A. Feofanova; G. V. Kontsevaya; M. V. Anisimova; I. I. Kovrigin; I. A. Serova; M. P. Moshkin; L. A. Gerlinskaya; N. R. Battulin (Вавиловский журнал генетики и селекции)
Transgenesis has become a routine for modern biological studies. The most popular method for producing transgenic animals–pronuclear microinjection–frequently leads to host gene disruption due to a random transgene integration. In this paper, we report our analysis of morphophysiological parameters of the transgenic mouse line GM9, in which a transgene designed for milk-specific expression of the human granulocyte-macrophage colony-stimulating factor (GM-CSF) gene was integrated into the intron of the Contactin 5 gene (Cntn5). We studied Cntn5 expression with RT-PCR and discovered that its expression in the brain, the primary organ of Cntn5 activity, was unperturbed. However, transgenic animals had less Cntn5 transcripts in other tissues such as the kidney and heart. In addition, we observed a decreased amount of splice variants of Cntn5 exons that flank the transgene integration site. These data suggest that the transgene integration event might affect proper Cntn5 splicing in some tissues. Publications exist that imply that some polymorphisms in the Cntn5 gene are associated with obesity and arterial hypertension in humans. We evaluated core parameters of lipid metabolism and heart activity in mice homozygous and heterozygous for Cntn5 mutation using wild- type animals as control. Our results uncovered that homozygous mutant mice have lower body weight than controls and that it is caused by slower accumulation of fat tissue. Cntn5 mutants also exhibit abnormalities in blood circulation: homozygous Cntn5 mutants are characterized by a higher blood pressure and heart beat rate, as well as faster blood flow in the tail vessels. Heterozygous animals showed intermediate results for all of these parameters.